Feasibility study of scapula bone as a next-generation material for biomedical applications - Tajammul Hussain Mysore; Arun Y. Patil; N. R. Banapurmath; Chandrashekhar Hegde; Raman Kumar; T. M. Yunus Khan (Journal of Applied Animal Research)
This study investigates the influence of material thickness on the mechanical properties, specifically flexural and tensile properties, of scapula bone specimens from Deccani breed sheep in India. A three-point bending test and a tensile test were conducted on samples with varying thicknesses (1, 2 and 5 mm), and the flexural strength, flexural modulus, ultimate load, tensile deformation and von Mises stress were measured. Thicker specimens exhibited higher flexural properties than thinner counterparts. Statistical analysis using one-way ANOVA confirmed that material thickness significantly impacted the flexural and tensile properties of the samples. Additionally, a simulation analysis was performed using ANSYS Workbench to validate the experimental results and provide insights into the tensile and flexural behaviour of the specimens. The findings suggest that thicker samples are better equipped to handle bending stresses and tensile loads and are more suitable for applications requiring resistance to bending loads, stiffness, load-bearing capacity and tensile strength.